Perilaku Birokrasi Dalam Peningkatan Kualitas Pelayanan Publik Pada Kantor Lurah Kambu Kota Kendari - Nega, Robinus; Amir, Muhammad; Abdullah, Akhyar (Universitas Halu Oleo, 2021)
The research is aimed to know the behavior of Bureaucracy In Improving Quality of Care Public on Office Lurah Kambu, District of Kambu City Kendari. Informants in penelitian it is numbered 6 people consisting of informants keys numbered 1 as Lurah Kambu city of Kendari, informant main numbered 1 as Sekertari Lurah, informants both amounted to 2 people as employees / staff k antor Lurah Kambu informant three numbered 2 people as a community that Have Problems ministry 2. The data obtained from the study is a good form of primary data and the data of secondary will be analyzed by descriptive qualitative. Results of the study is to show the behavior of the bureaucracy in the Improvement of the quality of service of the Public maintain and improved in giving out the behavior of the bureaucracy in the service of the public to the public so that the service remains running effectively, matter is seen from the quality of service of the public who are already giving out the services that the maximum and produce a quality of service that is effective. In the quality of service for Public Office Lurah Kambu , District of Kambu City K endari relatively quite good, things have proved of the five principles of service.